Features of eating behavior of students-athletes with different levels of will development - Petrova, E. A.; Kozyreva, V. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the specifics of the eating behavior of student-athletes with different levels of will development. Methods and structure of the study. 60 student-athletes aged 20 to 23 took part in the pedagogical experiment. To collect empirical material, we used: a block of methods for diagnosing willpower (test for determining willpower by R.S. Nemov; self-assessment test of willpower by N.N. Obozova) and a block of methods for diagnosing eating behavior (questionnaire "Eating behavior" by I.A. Savenkov (QEB); Eating Behavior questionnaire (EBQ); Dutch Eating Behavior questionnaire (GEBQ); Eating Attitude Test (EAT). Results and conclusions. The study found that student-athletes with a higher indicator of will development are characterized by harmonious eating behavior, accompanied by the ability to control themselves, their actions and the external manifestation of emotions, the ability to control their eating behavior in a social environment, and even in the most severe stressful situations. Student-athletes with a lower indicator of will development are characterized by the presence of disorders in eating behavior, accompanied by an increased reaction to external stimuli (external eating behavior), overeating in order to get rid of negative emotions (emotional eating behavior), as well as excessive food self-restriction and unsystematic strict diets (restrictive eating behavior).